2022
DOI: 10.1093/jamiaopen/ooac031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of explainable artificial intelligence assistance on clinical decision-making of novice dental clinicians

Abstract: Objective Despite artificial intelligence (AI) being used increasingly in healthcare, implementation challenges exist leading to potential biases during the clinical decision process of the practitioner. The interaction of AI with novice clinicians was investigated through an identification task, an important component of diagnosis, in dental radiography. The study evaluated the performance, efficiency, and confidence level of dental students on radiographic identification of furcation involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…More than two-thirds of the participants used AI assistants, with the majority among them using them more than ten times in the previous month indicating gradual penetration of AI assistants in family medicine. Similar results were identified in other studies focusing on specialties like cardiology and other healthcare departments on the use of AI assistants in clinical decision-making [ 27 - 30 ]. The results from the survey analysis have indicated various barriers and facilitators, which had a differential impact on the participants.…”
Section: Discussionsupporting
confidence: 89%
“…More than two-thirds of the participants used AI assistants, with the majority among them using them more than ten times in the previous month indicating gradual penetration of AI assistants in family medicine. Similar results were identified in other studies focusing on specialties like cardiology and other healthcare departments on the use of AI assistants in clinical decision-making [ 27 - 30 ]. The results from the survey analysis have indicated various barriers and facilitators, which had a differential impact on the participants.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, even though the difference in initial trust between novice and expert readers was not significant (adjusted p, 0.439; RBC, 0.15), the difference in final trust was instead significant (adjusted p, 0.009; RBC, 0.54), with the novice readers reporting, on average, a higher final trust than the expert ones. This is in line with previous studies in the field of human-AI interaction [23,24,41,42], which showed how novice readers are more willing to accept the support of an AI-based system, and better appreciate its output. An explanation for this widely reported observation can be traced back to the literature in the Theory of Technological Dominance (TTD) [39], in which a previous finding from Noga and Arnold [43] identified user expertise as one of the main determinants of dominance and reliance, of which trust is a determinant.…”
Section: Rq1-effect Of Expertise and Interaction Protocol On Trustsupporting
confidence: 91%
“…It has been demonstrated in similar studies that clinicians' behaviors change towards favoring AI when it is involved. 16,17 Prior research has noted that novice clinical practitioners often exhibit an over-reliance on AI. In this present study, a parallel over-reliance on AI was observed among the participating students.…”
Section: Discussionmentioning
confidence: 99%